(untitled) (Bangladesh Journal of Microbiology, 2010)
Longiverbenone is a naturally occurring sesquiterpene isolated from ethanolic extract of Cyperus scariosus rhizome by solvent-solvent portioning and chromatographic technique. The antibacterial activity of longiverbenone was evaluated against eleven potential human pathogenic bacteria using disc diffusion method. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined by broth macrodilution method. Cytotoxic activity (lethal concentration 50%, LC50) of longiverbenone was determined on new borne brine shrimp (Artemia salina). Longiverbenone showed moderate to good antibacterial activity against the test organisms tested herein. It exhibited the lowest MIC (20 μg/ml) and MBC (80 μg/ml) against Vibrio cholerae. The LC50 of the isolated sesquiterpene was found to be 14.38 μg/ml against new borne brine shrimp. Keywords: Antibacterial activity; Cytotoxic activity (LC50); Cyperus scariosu; Longiverbenone; Minimum inhibitory concentration (MIC) DOI: http://dx.doi.org/10.3329/bjm.v25i1.4866 Bangladesh J Microbiol, Volume 25, Number 1, June 2008, pp 82-84